Factors Affecting Technological Readiness and Acceptance of Induction Stoves: A Pilot Project - Retno W. Damayanti; Haryono Setiadi; Pringgo W. Laksono; Dania L. Rizky; Nisa A. E. Entifar (Emerging Science Journal, 2023)
In 2022, through the state electricity company, the Indonesian government launched a pilot experiment to cut imports of liquefied petroleum gas by giving program packages to 1,000 families in five districts in Surakarta. Objectives: Using the technology readiness and acceptance model (TRAM), this study examined the elements influencing the readiness and acceptability of the induction stove program in Surakarta. Method/Analysis: The empirical findings from a 389-respondent survey showed that the program’s public acceptance was supported by favorable technological preparedness, including elements like innovation and optimism. Findings: Perceived use, enjoyment, usefulness, cost level, and confirmation were all factors that affected participants' happiness and willingness to continue using induction stoves and participating in the program. Interestingly, acceptability, general contentment, and the willingness to use induction stoves were not always affected by issues like discomfort and insecurity. Additionally, this research emphasized how crucial the social context is for successfully implementing a program and embracing new technologies. Novelty:This is the first study that concurrently identifies, assesses, and analyzes the integration of factors impacting technology readiness and acceptance (TRAM) into the community's intention to continue participating in the induction stove conversion program. These empirical results offer practical guidance for stakeholders in induction stove conversion projects, particularly in developing nations, and also add to a theoretical understanding of TRAM factors. Doi: 10.28991/ESJ-2023-07-06-04 Full Text: PDF